Aircraft noise and self-assessed mental health around a regional urban airport: a population based record linkage study - David M. Wright; Katherine Newell; Aideen Maguire; Dermot O'Reilly (BMC, 2018)
Abstract Background Limited evidence suggests that residential exposure to aircraft noise negatively influences population mental health around large airports, but it is not known whether the same is true for smaller airports. We investigated whether residential exposure to aircraft noise near a regional urban airport was associated with risk of chronic self-assessed mental ill health. Methods This is a cross-sectional study of 198,532 people aged 18 years and over living in Belfast, United Kingdom, enumerated at the 2011 Census. Residential exposure to aircraft noise (LAeq,16h) was assessed by linking Census records with modelled noise contours surrounding George Best Belfast City Airport (c.42,000 annual aircraft movements). Associations between noise and mental ill health were estimated using multiple logistic regression adjusting for demographic characteristics, socio-economic status and comorbidity. Results Prevalence of self-assessed mental ill health was greater in high noise (≥57 dB) compared to low noise (< 54 dB) areas (12.4% vs. 9.7%). We found no association between aircraft noise and risk of mental ill health after adjustment for socio-economic status (high vs. low noise odds ratio: 1.03 CI: 0.93, 1.14). Discussion Associations between aircraft noise and mental health have been reported near large airports at similar average noise levels to those observed here. Our findings indicate that the noise environment around this smaller airport (with fewer flights and no night flights) has little influence on population mental health.